Upaya Deteksi Permasalahan Kesehatan Mental Siswa di SMPN 2 Kismantoro dengan Alat Skrining Perilaku Strength and Difficulties Questionnaire - Purwanta; Salsabila Firdausi Sudiro; Virginia Koeswardani, Hemalia Happy (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
This study aims to increase awareness of mental health among students at SMPN 2 Kismantoro using the Strength and Difficulties Questionnaire (SDQ) as a behavioral screening tool. The SDQ is used to evaluate emotional symptoms, behavioral problems, hyperactivity/inattention, peer relationship problems, and prosocial behavior in children and adolescents. The research was conducted through data collection, including observation, item reconstruction, questionnaire development, program implementation, analysis of the results, and reporting. The results show that most students have good mental health, but some need further attention and intensive monitoring to prevent the development of more serious mental health problems. Barriers to accessing mental health facilities, economic factors, and low mental health literacy are risk factors that need to be addressed. The results of this study can serve as a basis for developing more effective preventive programs to increase mental health awareness among students.